Decision and Game Theory in Management With Intuitionistic Fuzzy Sets - Li, Deng-Feng.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
The focus of this book is on establishing theories and methods of both decision and game analysis in management using intuitionistic fuzzy sets. It proposes a series of innovative theories, models and methods such as the representation theorem and extension principle of intuitionistic fuzzy sets, ranking methods of intuitionistic fuzzy numbers, non-linear and linear programming methods for intuitionistic fuzzy multi-attribute decision making and (interval-valued) intuitionistic fuzzy matrix games. These theories and methods form the theory system of intuitionistic fuzzy decision making and games, which is not only remarkably different from those of the traditional, Bayes and/or fuzzy decision theory but can also provide an effective and efficient tool for solving complex management problems. Since there is a certain degree of inherent hesitancy in real-life management, which cannot always be described by the traditional mathematical methods and/or fuzzy set theory, this book offers an effective approach to using the intuitionistic fuzzy set expressed with membership and non-membership functions. This book is addressed to all those involved in theoretical research and practical applications from a variety of fields/disciplines: decision science, game theory, management science, fuzzy sets, operational research, applied mathematics, systems engineering, industrial engineering, economics, etc.
Chapter 1 Intuitionistic Fuzzy Set Theories -- Chapter 2 Intuitionistic Fuzzy Set Aggregation Operators and Multiattribute Decision-Making Methods -- Chapter 3 Intuitionistic Fuzzy Set Multiattribute Decision-Making Methods -- Chapter 4 Interval-Valued Intuitionistic Fuzzy Set Multiattribute Decision-Making Methods -- Chapter 5 Multiattribute Decision-Making Methods Using Intuitionistic Fuzzy Numbers -- Chapter 6 Intuitionistic Fuzzy Set Multiattribute Group Decision-Making Methods -- Chapter 7 Intuitionistic Fuzzy Set Matrix Games and Linear or Nonlinear Programming Methods -- Chapter 8 Interval-Valued Intuitionistic Fuzzy Set Matrix Games and Linear or Nonlinear Programming Methods -- Chapter 9 Matrix Games with Payoffs of Intuitionistic Fuzzy Numbers and Solution Methods.
Keywords: Engineering; Mathematics; Algorithms; Economics, Mathematical; Operations research; Engineering; Computational Intelligence; Control; Algorithms; Game Theory/Mathematical Methods; Operation Research/Decision Theory; Game Theory, Economics, Social and Behav. Sciences